Parameters for Ramanujan’s function χ(q) of degree five and their explicit evaluation - Dharmendra, B. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the ratios of parameters for Ramanujan’s function χ(q) and their explicit values.